Determinant Factors of Knowledge about Obesity among Workers in the Chemical Industry in Surabaya City, East Java Province - Damayanti, Ratih; Lutfiya, Indah; Handayani, Nur Septia; Wardani, Ratnaningtyas Wahyu Kusuma; Linggarwati, Yunita Putri; Sweri, Anya Indras (Universitas Airlangga, 2024)
Introduction: Obesity is a health problem experienced by workers in the manufacturing industry. The incidence of obesity is caused by various factors, including lack of knowledge. This study aims to analyze the factors associated with knowledge about obesity among workers. Methods: This study an analytical observational design with a cross-sectional approach conducted at PT XYZ in Surabaya City, East Java Province. The population of this study consisted of 145 workers in the manufacturing sector from various work units. The sample size consisted of 119 people. The independent variables were age, sex, work tenure, work unit, education level, and access to information about obesity. Meanwhile, the dependent variable was knowledge level. The statistical test used was the contingency coefficient test. Results: The results showed that most workers were over the age of 35 years (89.9%), males (67.2%), worked in a production work unit (60.5%), had worked for more than 20 years (78.2%), had a high school degree (54.6%), had good knowledge (55.5%), and did not have access to information about obesity (55%). A relationship was found between work tenure (p = 0.001), education level (p = 0.002) and access to information (p = 0.004) with knowledge level of the workers about obesity. Meanwhile, age (p = 0.437), sex (p = 0.643), and work unit (p = 0.335) had no significant relationship with knowledge level of the workers about obesity. Conclusion: A relationship was found between work tenure, education level, and access to information with knowledge level about obesity.